Requiem or revival? the promise of North American integration - Studer-Noguez, Isabel, 1963-; Wise, Carol; ProQuest (Firm) (Washington, D.C. : Brookings Institution Press, 2007)
"Within NAFTA, explores interactions between regionalism and multilateralism, the impact of the "new trade" agenda, and unresolved problems--migration, security, and energy. Discusses NAFTA's relationship to the Free Trade Agreement of the Americas negotiations and the Doha Development Round and various ways in which NAFTA could be revamped or improved"--Provided by publisher.
1. No turning back : trade integration and the new development mandate / Carole Wise -- Part I, The North American Free Trade Area : Achievements and Limitations. 2. Unfulfilled promise : economic convergence under NAFTA / Carol Wise -- 3. Obstacles to integration : NAFTA's institutional weakness / Isabel Studer -- 4. Trade negotiations among NAFTA partners : the future of North American economic integration / Jeffrey J. Schott -- Part II, The Hemispheric Context : From NAFTA to the Free Trade Area of the Americas. 5. Beyond the FTAA : perspectives for hemispheric integration / Jaime Zabludovsky and Sergio Gomez Lora -- 6. The FTAA stalemate : implications for Canadian foreign policy / Gordon Mace -- 7. What went wrong? Brazil, the United States, and the FTAA / Glauco Oliveira -- Part III, The Global Context : The New Trade Agenda and the Doha Round. 8. The Doha Round : problems, challenges, and prospects / Theodore H. Cohn -- 9. U.S. trade politics during the Doha Round / I. M. Destler -- 10. Mexico in the multilateral trading system : a long and winding road / Antonio Ortiz Mena L. N. -- Part IV, Beyond Trade : Energy, Migration, and North American Integration. 11. The politics of energy markets in North America : challenges and prospects for a continental partnership / Isidro Morales -- 12. International energy security and North America / Charles F. Doran -- 13. North American immigration : the search for positive-sum returns / Tamara M. Woroby -- 14. Migration and citizenship rights in a new North American space / Christina Gabriel and Laura MacDonald.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Free trade -- North America; North America -- Economic integration; North America -- Economic policy; Electronic books